Reconstruction of Islamic Religious Education to Encountering Terrorism and Islamic Radicalism (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The aim of this research is to explain the importance of reconstructing Islamic Religious Education (hereafter IRE) by creating tolerant and inclusive teachers. Besides that, this research also describes some steps which can be done by teachers in fighting terrorism and radicalism. This is literature research. The data was collected through the documentation method. These research findings revealed that the reconstruction of IRE is important and urgent to do. Recently, IRE is not effective enough to produce a tolerant and inclusive person. It can be seen that many terrorism perpetrators and Islamic radicalism are from both senior high school and university students. Besides that, the failure can be also observed from the result of the institution’s survey showing the low level of tolerance among students. Reconstruction of IRE covers some aspects such as curriculum, teacher, material, method, media, and evaluation. Without ignoring other aspects, IRE teachers have an important role in fighting terrorism and radicalism. It is to those who have tolerant and inclusive character. To yield a tolerant and inclusive person, it needs contribution from some parties such as higher education institutions, government, and society. There are some steps that can be taken by IRE teachers in fighting terrorism and radicalism, namely: (1) IRE teachers must be able to create a multicultural atmosphere; (2) IRE teachers must become good figures for their student’s concerning tolerance. The significant role of IRE teachers is expected to eradicate terrorism and radicalism at the educational institution level. If IRE teachers are not inclusive, IRE will be a good place to rise terrorism and Islamic radicalism.